Literasi Keamanan Siber UMKM Diaspora Indonesia–China melalui Pelatihan Anti-Penipuan Berbasis GIS - Aziz, Muhammad; Umar, Rusydi; Ibdal (LPPM UMRI, 2026)
Abstract The growth of cross-border digital trade creates economic opportunities for Indonesian–Chinese diaspora Micro, Small, and Medium Enterprises (MSMEs), while increasing exposure to online fraud, phishing, invoice manipulation, and digital identity misuse. Limited cybersecurity literacy constrains MSMEs’ capabilities in supplier verification, account protection, and international transaction risk mitigation. This community service program aimed to strengthen the digital security capacity of diaspora MSMEs through Geographic Information System (GIS)-based anti-fraud training. A participatory approach was employed, including needs assessment, GIS-based digital risk mapping, bilingual Indonesian–Mandarin module development, international hybrid training, anti-fraud simulations, cyber hygiene clinics, and implementation assistance. Key technologies included Digital Threat Mapping, a Digital Vulnerability Assessment (DVA) Dashboard, and Standard Operating Procedures (SOPs) for cross-border transaction verification. Results demonstrated improved participant understanding of phishing prevention, account security, two-factor authentication (2FA), and digital supplier verification. GIS visualization identified digital threat hotspot patterns between Indonesia and China, while the DVA Dashboard enabled participants to conduct independent cybersecurity vulnerability assessments. The program demonstrates that integrating cybersecurity literacy, spatial analysis, and digital ethics can enhance diaspora MSMEs’ resilience within the global digital economy ecosystem. Keywords: Cybersecurity Literacy; GIS-Based Risk Mapping; Cross-Border Digital Trade; Diaspora MSMEs; Digital Security